2022
DOI: 10.21203/rs.3.rs-1876968/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wetland conservation and management practices in Rubanda District, South-Western Uganda

Abstract: Worldwide, wetlands cover about 9% of the land surface and are recognized as bio-networks that offer living prospects when managed properly. Despite the present resource management regime, many wetlands in Uganda are being degraded due to mining, construction, agricultural and industrial activity, and little attention has been paid to the effectiveness of wetland conservation. The goal of this research was to evaluate Nyamuriro wetland conservation and management practices in Rubanda District, Uganda. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The second objective of this study sought to assess the effect of the auditing process on service delivery at Kabale District Local Government (John Moses & Turyasingura, 2022a;Turyasingura & Moses, 2023). When data was collected and analysed, results indicated that there was a positive and significant relationship between the two variables.…”
Section: Discussionmentioning
confidence: 99%
“…The second objective of this study sought to assess the effect of the auditing process on service delivery at Kabale District Local Government (John Moses & Turyasingura, 2022a;Turyasingura & Moses, 2023). When data was collected and analysed, results indicated that there was a positive and significant relationship between the two variables.…”
Section: Discussionmentioning
confidence: 99%
“…Reliability evaluations look at how consistently the measuring tools give results when the same populations of people are repeatedly measured under the same circumstances (Wilberforce et al, 2021;Turyasingura et al (2022). A pilot study with respondents who were purposefully and simply chosen at random from the target area is also used to test the validity of the research tools.…”
Section: Reliabilitymentioning
confidence: 99%
“…A random sampling technique was used to select the population [20]. Random sampling was used because it helps to capture information from the available population at the time of research [21].…”
Section: Sampling Techniquesmentioning
confidence: 99%